ANALISIS FORMAL SENI LUKIS KARYA SOEGENG TOEKIO TAHUN 2000-2015 - Isnanta, Satriana Didiek (Institut Seni Indoensia Surakarta, 2015)
This article discusses the formal aesthetic work Soegeng Toekio years 2000-2015. It is based on the understanding that the aesthetic value of a work of art can be formed by the work itself, and standard views deserve is requiring the work itself, rather than coming from outside work which is seen as an extra factor aesthetic.The approach used is the aesthetic approach using aesthetic theory by De Witt H. Parker, in his book The Principles of Aesthetics (1920), quoted by The Lian Gie in the book